The Civil War volume 1 [videorecording (DVD)] : a film by Ken Burns - Burns, Ken, 1953-; McCullough, David G.; Burns, Ric; Dewhurst, Colleen; Fishburne, Larry; Freeman, Morgan; Harris, Julie; Irons, Jeremy, |d1948-; Jacobi, Derek, |d1938-; Keillor, Garrison; Robards, Jason; Terkel, Studs, |d1912-2008; et al. (PBS Home Video, 1990)
This landmark documentary film series movingly and vividly presents the entire sweep of the war, from the battlefields to the homefronts, from the politicians and generals to the enlisted men and their families, from the causes of the war and the opening guns at Sumter to the stillness at Appomattox and Lincoln's assassination and beyond.